Seeing after the End: Promesas naturales [Natural Promises] by Oliverio Coelho - Catalin, Mariana (Universidad Pedagógica y Tecnológica de Colombia, 2018)
Promesas naturales is the third episode of a trilogy published by Oliverio Coelho between 2003 and 2006. As with the first two episodes, Los invertebrables and Borneo , the saga’s last avatar constructs the future by tensing the immanent time of crises against a horizon of radical end that question it. In the broader context of research on post-apocalyptic imaginaries in recent Argentinian narrative, the present work analyzes the particular way in which, Promesas naturales stratifies temporalities, based on that tension. In order to account for this singularity we examine the modes of articulation of vision, biological mutation, State control mechanisms and territorial limits